Gender differences in children's pedestrian behaviors: Developmental effects. (December 2018) - Wang, Huarong; Schwebel, David C.; Tan, Dingliang; Shi, Licheng; Miao, Lvqing
Abstract: Introduction: All child pedestrians are vulnerable to road traffic injuries, but there is evidence that boys may be at greater risk than girls, at least among some age groups. Method: To create effective intervention programs, research on how boys and girls of particular ages behave as pedestrians, and whether there are gender differences that increase risk for particular genders at particular ages, is needed. In this study, 255 boys and 235 girls in grade 1 through 6 from two primary schools in Nantong city, China, were unobtrusively videotaped when walking to school in the morning. Videotapes were reviewed and coded for seven pedestrian safety behaviors, including activities related to crossing streets (walking instead of running/hopping, observing traffic, using the crosswalk instead of walking outside the crosswalk, and keeping close to an accompanying adult) and those related to walking alongside busy streets (walking instead of running/hopping on the sidewalk, not playing on the sidewalk, walking alone instead of walking side-by-side with a partner). Results: Results revealed that as a whole, boys played on the sidewalk more often than girls (p < 0.01) and crossed with an accompanying adult more than girls (p < 0.05), while girls walked side-by-side with partners more often than boys (p < 0.05). With a few exceptions, boys and girls in the younger grades (1–2) as well as those in the older grades (5–6) behaved fairly similarly as pedestrians, but boys and girls in the middle grades (3–4) presented with several significant gender-based differences. In the middle grades, boys watched traffic more than girls while crossing (p < 0.01); ran, hopped and played on the sidewalk more often than girls (p < 0.05); and walked side-by-side less often with partners than girls (p < 0.05). We also detected different gender-based trends in the development of pedestrian skills. With increasing age, girls performed more safely in pedestrian tasks, but boys did not show a similar developmental trend. Conclusions: We conclude that boys and girls exhibit different characteristics in their pedestrian behaviors and discuss implications for prevention. Highlights: Gender differences of pedestrian behaviors among children in grades one through six are studied by observing. Across the full sample, few gender differences emerged in crossing behaviors. Boys and girls in the younger grades (1–2) as well as those in the older grades (5–6) behaved fairly similarly as pedestrians. Boys and girls in the middle grades (3–4) presented with several significant gender-based differences. With increasing age, girls performed more safely in pedestrian tasks, but boys did not show a similar developmental trend.